Increased Number of Fetal Nucleated Red Blood Cells in the Placentas of Term or Near-Term Stillborn and Neonates Correlates with the Presence of Diffuse Intradural Hemorrhage in the Perinatal Period. (January 2014) - Cohen, Marta C.; Peres, Luiz C.; Al-Adnani, Mudher; Zapata-Vázquez, Rita
Release of nucleated red blood cells (nRBCs) into the peripheral blood occurs in stillbirths/neonates with a probable hypoxic mode of death and antenatal stress. We correlated the number of nRBCs in the placenta with the occurrence of intradural (IDH) and subdural hemorrhage (SDH) and the potential link with fetal hypoxia. Two groups of 22 cases each of nonmacerated term or near-term (≥36 weeks of gestational age) stillborn or newborns dying in the 1st day of life were studied. One group had IDH (with or without SDH) and the other did not have IDH or SDH. In each case, the number of nRBCs was determined in 10 consecutive placental fields at ×40. Data were analyzed with Fisher exact test, receiver operating characteristic (ROC) curve analysis, and logistic regression. There was a significant association between the diffuse IDH and increased number of nRBCs (Fisher exact test P = 0.0165). An ROC curve analysis showed that the cut-off number of nRBCs with the highest accuracy was 2.15 nRBCs/high-power field, with 79% sensitivity and 67% specificity. The presence of diffuse IDH was associated with SDH (Fisher exact test, P = 0.002). The absence of hypoxic brain change was associated with the absence of diffuse IDH (odds ratio 0.308; P = 0.039). We established a significant correlation between the release of nRBCs into the placental circulation and the occurrence of diffuse IDH and between diffuse IDH and the presence of SDH.